Age-Related Changes in Reasons for Using Alcohol and Marijuana From Ages 18 to 30 in a National Sample - Patrick, Megan E. (2011)
This study used up to seven waves of data from 32 consecutive cohorts of participants in the national longitudinal Monitoring the Future study to model changes in self-reported reasons for using alcohol and marijuana by age (18 to 30), gender, and recent substance use. The majority of stated reasons for use decreased in prevalence across young adulthood (e.g., social/recreational and coping with negative affect reasons); exceptions included age-related increases in using to relax (alcohol and marijuana), to sleep (alcohol), because it tastes good (alcohol), and to get high (marijuana). Women were more likely than men to report drinking for reasons involving distress (i.e., to get away from problems), while men were more likely than women to endorse all other reasons. Greater substance use at age 18 was associated with greater likelihood of all reasons except to experiment and to fit in. A better understanding of developmental changes in reasons for use is important for understanding normative changes in substance use behaviors and for informing intervention efforts involving underlying reasons for use.